Impact of dietary nitrate supplementation on exercise capacity and cardiovascular parameters in chronic respiratory disease: a systematic review and meta-analysis - Michael I Polkey; Nicholas S Hopkinson; Saeed M Alghamdi; Ali M Alasmari; Abdullah S Alsulayyim (BMJ Open Respiratory Research)
Background Dietary nitrate supplementation, usually in the form of beetroot juice, may improve exercise performance and endothelial function. We undertook a systematic review and meta-analysis to establish whether this approach has beneficial effects in people with respiratory disease.Methods A systematic search of records up to March 2021 was performed on PubMed, CINAHL, MEDLINE (Ovid), Cochrane and Embase to retrieve clinical trials that evaluated the efficacy of dietary nitrate supplementation on cardiovascular parameters and exercise capacity in chronic respiratory conditions. Two authors independently screened titles, abstracts and full texts of potential studies and performed the data extraction.Results After full-text review of 67 papers, eleven (two randomised controlled trials and nine crossover trials) involving 282 participants met the inclusion criteria. Three were single dose; seven short term; and one, the largest (n=122), done in the context of pulmonary rehabilitation. Pooled analysis showed that dietary nitrate supplementation reduced systolic blood pressure (BP), diastolic BP and mean arterial pressure (mean difference (95% CI), −3.39 mm Hg (−6.79 to 0.01); p=0.05 and –2.20 mm Hg (−4.36 to −0.03); p=0.05 and −4.40 mm Hg (−7.49 to −1.30); p=0.005, respectively). It was associated with increased walk distance in the context of pulmonary rehabilitation (standardised mean difference (95% CI), 0.47 (0.11 to 0.83), p=0.01), but no effect was identified in short-term studies (0.08 (−0.32 to 0.49).Conclusion Dietary nitrate supplementation may have a beneficial effect on BP and augment the effect of pulmonary rehabilitation on exercise capacity. Short-term studies do not suggest a consistent benefit on exercise capacity.PROSPERO registration number CRD42019130123.